(untitled) (The Review of Diabetic Studies, 2025)
Acute gastroenteritis (AGE) remains a leading cause of dehydration and hospitalization among children worldwide. Accurate identification of clinical and laboratory predictors of severe dehydration is essential for timely management and improved outcomes. Objectives: This systematic review aimed to synthesize evidence on clinical, biochemical, and epidemiological predictors of dehydration severity and related outcomes—including hospital admission, recurrence, electrolyte imbalance, and mortality—among pediatric AGE cases. Methods: Following PRISMA 2020 guidelines, 11 peer-reviewed studies published between 2008 and 2025 were analyzed. Studies included prospective cohorts, cross-sectional analyses, and secondary data from randomized trials focusing on predictors of dehydration in children aged 0–18 years with AGE. Data were extracted on demographic characteristics, dehydration indicators, and clinical outcomes. Results: Across studies, sunken eyes, poor skin turgor, and prolonged capillary refill time were the most consistent clinical predictors of severe dehydration. Biochemical abnormalities such as hyponatremia, low bicarbonate (<18 mmol/L), and metabolic acidosis were significant laboratory correlates. Younger age, delayed presentation, and inadequate oral rehydration therapy increased the risk of hospitalization. Predictive scoring systems like the Clinical Dehydration Scale (CDS) and Pediatric Acute Gastroenteritis Risk Score demonstrated moderate diagnostic performance. Conclusion: Accurate clinical evaluation complemented by simple laboratory parameters can effectively predict severe dehydration and guide management in pediatric AGE. Future studies integrating machine learning models and large-scale validation across regions are warranted.